2021
DOI: 10.2147/jir.s312091
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cytokines Elevated in Patients with Keloids: Is It an Indication of Auto-Inflammatory Disease?

Abstract: Background Inflammation seems to play a major role in the pathophysiology of keloids. However, the role of cytokines in keloid pathophysiology has not been fully evaluated with only a few cytokines studied. We undertook this study to compare various cytokines in patients with keloids and a control group of patients without keloids nor family history of keloids so as to determine which cytokines are elevated and could thus be critical in keloid formation. Methods This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In addition to the evidence indicating that IL-17-producing Th17 cells stimulate keloid formation, we also found Th2 cells producing IL-4 and IL-13 in the immune infiltrates, which are considered important mediators in the pathogenesis of fibroproliferative diseases such as sclerodermalike cutaneous syndromes (35), abnormal scarring (36) and keloid formation (37). Furthermore, a recent cross-sectional study by Nangole et al (38) showed that IL-4, IL-13 and a variety of other cytokines were significantly elevated in the plasma of keloid patients compared with normal subjects, leading the authors to speculate that the immune system plays a role similar to that of autoinflammatory disease in the formation of keloid. Among the DEGs involved in the IL-13 signaling pathway identified by the KEGG analysis, CXCL8 was recently confirmed to play an important role in keloid scar formation (39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the evidence indicating that IL-17-producing Th17 cells stimulate keloid formation, we also found Th2 cells producing IL-4 and IL-13 in the immune infiltrates, which are considered important mediators in the pathogenesis of fibroproliferative diseases such as sclerodermalike cutaneous syndromes (35), abnormal scarring (36) and keloid formation (37). Furthermore, a recent cross-sectional study by Nangole et al (38) showed that IL-4, IL-13 and a variety of other cytokines were significantly elevated in the plasma of keloid patients compared with normal subjects, leading the authors to speculate that the immune system plays a role similar to that of autoinflammatory disease in the formation of keloid. Among the DEGs involved in the IL-13 signaling pathway identified by the KEGG analysis, CXCL8 was recently confirmed to play an important role in keloid scar formation (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent cross-sectional study by Nangole et al. ( 37 ) showed that IL-4, IL-13 and a variety of other cytokines were significantly elevated in the plasma of keloid patients compared with normal subjects, leading the authors to speculate that the immune system plays a role similar to that of autoinflammatory disease in the formation of keloid. Among the DEGs involved in the IL-13 signaling pathway identified by the KEGG analysis, CXCL8 was recently confirmed to play an important role in keloid scar formation ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the immune system plays an indispensable role in keloid development. Additionally, keloid formation is closely related to inflammatory responses, especially inflammation-related factors, such as interleukin 6, transforming growth factor-β, and tumor necrosis factor-α and inflammation-related cells, such as neutrophils, mast cells, and lymphocytes ( 73 ). The inflammatory response is an adaptive response to adverse stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identifying signal pathways underlying fibrogenesis of keloid fibroblasts may shed light on novel therapeutic strategies. IL13 , a key driver of progressive fibrosis (11)(12)(13), has been found to be elevated in keloid patients (14). IL13 has also been reported to induce production of anti-apoptotic proteins and directly enhance myofibroblast function.…”
Section: Introductionmentioning
confidence: 99%
“…IL-13, a key driver of progressive fibrosis ( 11 13 ), has been found to be elevated in keloid patients ( 14 ). IL-13 has also been reported to induce production of antiapoptotic proteins and directly enhance myofibroblast function.…”
Section: Introductionmentioning
confidence: 99%